Common Supplements in Plant-Based Nutrition: Dosing, Formulations, and Safety - Sneha Baxi Srivastava (American Journal of Lifestyle Medicine, 2026)
Dietary supplements are commonly used to support health and athletic performance. This article provides practical guidance for evaluating supplement quality, labeling, formulations, and ingredients, with particular attention to plant-based products. Creatine, caffeine, and beta-alanine are highlighted to illustrate differences in available formulations, dosing considerations, safety, and potential non-vegan ingredients. Health care professionals can use this information to help individuals select supplements that align with their health needs, goals, preferences, and values.